The energy spectra of the graphene-based quasi-periodic superlattice - Korol, A.M.; Sokolenko, A.I.; Sokolenko, I.V. (Физика низких температур, 2018)
The spectra of the Dirac quasi-electrons transmission through the Fibonacci quasi-periodical superlattice (SL) are calculated and analyzed in the continuum model with the help of the transfer matrix method. The one-dimensional SL based on a monolayer graphene modulated by the Fermi velocity barriers is studied. A new quasi-periodical factor is proposed to be considered. We show that the Fibonacci quasi-periodic modulation in graphene superlattices with the velocity barriers can be effectively realized by virtue of a difference in the velocity barrier values (no additional factor is needed and we keep in mind that not each factor can provide the quasi-periodicity). This fact is true for a case of normal incidence of quasi-electrons on a lattice. In contrast to the case of other types of the graphene SL spectra studied reveal the remarkable property, namely the periodic character over all the energy scale and the transmission coefficient doesn’t tend asymptotically to unity at rather large energies. Both the conductance (using the known Landauer–Buttiker formula) and the Fano factor for the structure considered are also calculated and analyzed. The dependence of spectra on the Fermi velocity magnitude and on the external electrostatic potential as well as on the SL geometrical parameters (width of barriers and quantum wells) is analyzed. Using the quasi-periodical SL one can control the transport properties of the graphene structures in a wide range. The obtained results can be used for applications in the graphene-based electronics. В континуальній моделі методом трансферних
матриць розраховано та проаналізовано спектри
трансмісії діраківських квазіелектронів крізь квазіперіодичну надгратку (НГ) Фібоначчі. Розглядається одновимірна НГ на основі моношарового
графену, модульована бар’єрами швидкості Фермі. Запропоновано використати новий квазіперіодичний фактор. Показано, що квазіперіодична
модуляція Фібоначчі в графенових надгратках із
бар’єрами швидкості Фермі може бути ефективно
реалізована завдяки різниці в значеннях бар’єрів
цієї швидкості (додатковий фактор не потрібен, і
слід зазначити, що не кожен фактор може забезпечити квазіперіодичну модуляцію). Цей факт
справедливий для випадку нормального падіння
квазіелектронів на гратку. На відміну від інших
типів вивчених спектрів трансмісії в графенових
НГ в даному випадку виявляється нетривіальна їх
властивість — періодичність по всій шкалі енергії, так що коефіцієнт пропускання не наближається асимптотично до одиниці при достатньо високих енергіях. Розраховано та проаналізовано
провідність (з використанням відомої формули
Ландауера–Буттікера) та фактор Фано для даної
структури. Проаналізовано залежність спектрів
від величини швидкості Фермі та від зовнішнього
електростатичного потенціалу, а також від геометричних параметрів НГ (ширин бар’єрів і квантових ям). Використовуючи розглянуті квазіперіодичні НГ, можна регулювати транспортні
властивості графенових структур в широкому діапазоні їх параметрів. Отримані результати можуть бути використані для застосування в електроніці на основі графену.